PENGUKURAN PRODUKTIVITAS INDUSTRI KERIPIK TEMPE SUKA NICKY MENGGUNAKAN METODE APC (THE AMERICAN PRODUCTIVITY CENTER) - , YANTI NOPIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Suka Nicky industry is one of the industries that works on food processing that focuses on processing soy beans into tempe chips. This study aims at measuring the industry productivity using the APC (The American Productivity Center) methods during the period of JulyâDecember 2013. There are five criteria measured in this study, i.e. the total productivity, labor work productivity, raw material productivity, energy productivity, and the capital productivity. Based on the measurement result, the decline was found on the level of the industry total productivity from the period of July up to December, 2013. The total productivity indexs decreased into 86.9135 in August, 78.7955 in the period of October, 72.1298 on the period of November, and into 76.7227 in the period of December.